Feasibility and safety of planned early discharge following laparotomy in gynecologic oncology with enhanced recovery protocol including opioid-sparing anesthesia - Kuznicki, Michelle L.; Yasukawa, Maya; Mallen, Adrianne R.; Lam, Clarissa; Eggers, Erica; Regis, Jefferson; Wells, Ali; Todd, Sarah L.; Robertson, Sharon E.; Tanner, Jean-Paul; Anderson, Matthew L.; Rutherford, Thomas J. (Frontiers in Surgery, 2023)
Objective This study aims to evaluate the feasibility and safety of planned postoperative day 1 discharge (PPOD1) among patients who undergo laparotomy (XL) in the department of gynecology oncology utilizing a modified enhanced recovery after surgery (ERAS) protocol including opioid-sparing anesthesia (OSA) and defined discharge criteria. Methods Patients undergoing XL and minimally invasive surgery (MIS) were enrolled in this prospective, observational cohort study after the departmental implementation of a modified ERAS protocol. The primary outcome was quality of life (QoL) using SF36, PROMIS GI, and ICIQ-FLUTS at baseline and 2- and 6-week postoperative visits. Statistical significance was assessed using the two-tailed Student's t-test and non-parametric Mann–Whitney two-sample test. Results Of the 141 subjects, no significant demographic differences were observed between the XL group and the MIS group. The majority of subjects, 84.7% (61), in the XL group had gynecologic malignancy [vs. MIS group; 21 (29.2%), p < 0.001]. All patients tolerated OSA. The XL group required higher intraoperative opioids [7.1 ± 9.2 morphine milligram equivalents (MME) vs. 3.9 ± 6.9 MME, p = 0.02] and longer surgical time (114.2 ± 41 min vs. 96.8 ± 32.1 min, p = 0.006). No significant difference was noted in the opioid requirements at the immediate postoperative phase and the rest of the postoperative day (POD) 0 or POD 1. In the XL group, 69 patients (73.6%) were successfully discharged home on POD1. There was no increase in the PROMIS score at 2 and 6 weeks compared to the preoperative phase. The readmission rates within 30 days after surgery (XL 4.2% vs. MIS 1.4%, p = 0.62), rates of surgical site infection (XL 0% vs. MIS 2.8%, p = 0.24), and mean number of post-discharge phone calls (0 vs. 0, p = 0.41) were comparable between the two groups. Although QoL scores were significantly lower than baseline in four of the nine QoL domains at 2 weeks post-laparotomy, all except physical health recovered by the 6-week time point. Conclusions PPOD1 is a safe and feasible strategy for XL performed in the gynecologic oncology department. PPOD1 did not increase opioid requirements, readmission rates compared to MIS, and patient-reported constipation and nausea/vomiting compared to the preoperative phase.